2014
DOI: 10.1021/jp5008472
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Surface Reactions and Adsorption Studied on Y2O3, YSZ, and ZrO2

Abstract: The surface reactivity of Y2O3, YSZ, and ZrO2 polycrystalline powder samples toward H2 has been comparatively studied by a pool of complementary experimental techniques, comprising volumetric methods (temperature-programmed volumetric adsorption/oxidation and thermal desorption spectrometry), spectroscopic techniques (in situ electric impedance and in situ Fourier-transform infrared spectroscopy), and eventually structural characterization methods (X-ray diffraction and scanning electron microscopy). Reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 29 publications
(58 reference statements)
2
52
0
Order By: Relevance
“…A small shoulder in the water formation curves at 350 °C can be detected also over the doped catalysts. It has been reported by Kogler et al [27] that over Y 2 O 3 -ZrO 2 water desorption can be observed even after reduction and evacuation. The water desorption is related to the dehydroxylation of the Y 2 O 3 -ZrO 2 surface.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A small shoulder in the water formation curves at 350 °C can be detected also over the doped catalysts. It has been reported by Kogler et al [27] that over Y 2 O 3 -ZrO 2 water desorption can be observed even after reduction and evacuation. The water desorption is related to the dehydroxylation of the Y 2 O 3 -ZrO 2 surface.…”
Section: Discussionmentioning
confidence: 91%
“…The model underestimates also the formation of water between 350-550 °C. Water desorption from reduced (at 400 °C) and evacuated (at room temperature) surface of Y 2 O 3 -ZrO 2 has been reported to have maxima at 427 °C by Kogler et al [27]. Thus, it can be suggested that in toluene oxidation experiments, the formation of water at 350-550 °C is due to the water desorption from the surface of Y 2 O 3 -ZrO 2 as well as from toluene oxidation as a product.…”
Section: Discussionmentioning
confidence: 96%
“…the sample with the highest degree of hydration, a new low-temperature release of water and CO is observed. Finally, all samples release concurrently CO and H 2 O at around 400°C, as well as CO 2 and H 2 at above 500°C. It can be noted that the effect of surface hydration is mainly seen in the low temperature window since the high-temperature processes do not differ greatly [14].…”
Section: Wgs; Formate Chemistry and Reactivitymentioning
confidence: 92%
“…However, it is claimed that surface oxygen can be removed in vacuum at temperatures above 700°C [1,2]. Reduction of ZrO 2 has been suggested to follow a mechanism according to which surface OH groups formed by dissociatively activated hydrogen react to form water, and therefore the role of OH groups in directing the catalytic properties of the oxide should be considered [2]. So, reactivity of surface oxygen on ZrO 2 is connected to the formation of OH groups, which will always be present on the surface under conditions relevant to catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…This is related to the fact that single crystals of pure ZrO 2 grown from the melt exhibit phase transformations upon cooling, thus only crystals of doped zirconia (e.g., YSZ) are available; these retain the hightemperature cubic phase. The surface chemistry of YSZ is much more complex than that of pure ZrO 2 , however, as shown for adsorption of H 2 O, 24 hydrogen, 25 or CO and CO 2 . 26 Therefore, the investigation of pure ZrO 2 , which is needed as a starting point of a well-grounded fundamental understanding, has to rely on thin lms.…”
Section: Introductionmentioning
confidence: 99%